The Reflection of Liberal Feminism Values in the Characterization of Merida in Brave Movie - Pandini, Komang Tria; I Gusti Ayu Vina Widiadnya Putri (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This study analyzes the reflection of liberal feminism values in the characterization of Merida in the movie Brave. Feminism, particularly liberal feminism, emphasizes individual freedom, equal rights, and personal autonomy, making it relevant to Merida’s character, who opposes traditional norms and refuses an arranged marriage. This research employs the liberal feminism theory proposed by Tong (2008) to identify the values of equality and liberty in Merida’s character. The analysis also uses Boggs and Petrie’s (2018) theory of characterization, focusing on four aspects: appearance, dialogue, external actions, and the reactions of other characters. Data were collected using observation and note-taking techniques by watching the movie and reading the script. The findings were analyzed qualitatively by identifying scenes and dialogues that portray liberal feminist values. The results show that Merida represents liberal feminism through her resistance to patriarchal traditions, her fight for autonomy, and her assertion of individual rights. This research is expected to contribute theoretically to studies in literature and gender, especially in exploring feminist themes in film, and practically to help readers recognize and understand the importance of equality and freedom in society. Keywords: Liberal Feminism, Characterization, Merida, Brave Movie, Equality